Ethyl Pyruvate Ameliorates Hepatic Ischemia-Reperfusion Injury by Inhibiting Intrinsic Pathway of Apoptosis and Autophagy - Miao Shen; Jie Lu; Weiqi Dai; Fan Wang; Ling Xu; Kan Chen; Lei He; Ping Cheng; Yan Zhang; Chengfen Wang; Dong Wu; Jing Yang; et al. (Hindawi Limited, 2013)
Background. Hepatic ischemia-reperfusion (I/R) injury is a pivotal clinical problem occurring in many clinical conditions such as transplantation, trauma, and hepatic failure after hemorrhagic shock. Apoptosis and autophagy have been shown to contribute to cell death in hepatic I/R injury. Ethyl pyruvate, a stable and simple lipophilic ester, has been shown to have anti-inflammatory properties. In this study, the purpose is to explore both the effect of ethyl pyruvate on hepatic I/R injury and regulation of intrinsic pathway of apoptosis and autophagy. Methods. Three doses of ethyl pyruvate (20 mg/kg, 40 mg/kg, and 80 mg/kg) were administered 1 h before a model of segmental (70%) hepatic warm ischemia was established in Balb/c mice. All serum and liver tissues were obtained at three different time points (4 h, 8 h, and 16 h). Results. Alanine aminotransferase (ALT), aspartate aminotransferase (AST), and pathological features were significantly ameliorated by ethyl pyruvate (80 mg/kg). The expression of Bcl-2, Bax, Beclin-1, and LC3, which play an important role in the regulation of intrinsic pathway of apoptosis and autophagy, was also obviously decreased by ethyl pyruvate (80 mg/kg). Furthermore, ethyl pyruvate inhibited the HMGB1/TLR4/ NF-κb axis and the release of cytokines (TNF-α and IL-6). Conclusion. Our results showed that ethyl pyruvate might attenuate to hepatic I/R injury by inhibiting intrinsic pathway of apoptosis and autophagy, mediated partly through downregulation of HMGB1/TLR4/ NF-κb axis and the competitive interaction with Beclin-1 of HMGB1.